Hubungan antara Latar Belakang Keluarga dengan Pencapaian Akademik Pelajar Melayu dalam PMR - Zukina, Yusoff (2003)
The general aim of this research was to determine the correlation between family background and academic achievements of the Malay students in PMR (Penilaian Menengah Rendah). A total of 200 respondents from 4 different schools, representing the rural and urban categories, was selected. The family background includes the parents' level of education, their occupation, income, family size, family structure and family environment. The students' academic achievements were based on the PMR results. The Pearson Correlation an independent t-test were used to test the hyphothesis in the study. Thee results from the Pearson Correlation showed a significant difference between the family background and students' achievements. However the family structure has no influence on their achievements. The t-test analysis showed that there was a significant difference between the rural and urban students in terms of academic achievement. The research clearly indicated that family factor plays an important role in determining the students' achievements in education.